Respuesta :

Let's find out by replacing d with -12. Then we'll simplify the left side

|d+9| = 3

|-12+9| = 3 .... replace d with -12

|-3| = 3

3 = 3

Since we get a true statement, ie the same thing on both sides, this means the original equation is true when d = -12.

Therefore d = -12 is one of the two solutions to the original equation.

Answer: True

Answer:

True

Step-by-step explanation:

We can check this by substituting x = - 12 into the left side of the equation. If the result is equal to the right side then it is a solution.

| - 12 + 9 | = | - 3 | = 3 = right side

Thus x = - 12 is one of the solutions to the equation.

[ The other solution is x = - 6 ]